Grammatical influence of spanish in adult EFL learners - Álvarez Romero, Alvaro Felipe; Vanegas Pesántez, Mayra Ivón
The following study is designed to determine the way how adult EFL learners are influenced by their native language (L1) when learning the foreign language (L2), with particular focus on the grammatical aspects of both languages. It aims to analyze the students? perceptions regarding the importance of L1 and L2 grammar for in terms of the L2 learning process. It also analyzes the extent to which this specific group of language learners may benefit from comparing L1 and L2 grammar for purposes of learning. The literary review in this work provides a general idea of the status of L1 influence on L2 in the adult EFL learning process. In addition, a study has been conducted on 9 adult EFL learners from the Universidad Del Azuay in order validate what has been stated by the theory. The findings demonstrate that most adults customarily rely on their L1 in order to communicate in the L2. Additionally, they seem to be highly affected by the grammar of their L1 when using the L2. By analyzing the learners? written tasks, it has been concluded that their lack of grammatical accuracy as well as transfer from the L1, caused a great deal of errors in the L2. This could be undoubtedly avoided if the learners were made aware of both the similarities and the differences in the language patterns between the two languages.